To Tackle C0 2, Start with H20: How Latin America's Water Problems Could Affect Climate Change Negotiations - Moreno, Luis Alberto (Tufts Archival Research Center, 2005)
Volume 34, Issue 2. Summer Despite its economic reliance on water resources, Latin America is especially vulnerable to disturbances in water supplies resulting from global climate change. President of the Inter-American Development Bank Luis Alberto Moreno therefore sees a unique opportunity to re-engage Latin American policymakers in global climate negotiations.